PENGARUH KUALITAS PRODUK, HARGA, BRAND IMAGE DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MS GLOW - Ratuliu, Novika Jesya; Pratama, Maulana Agung; Adistya, Diang (Jurnal Kompetitif Bisnis, 2025)
This study aims to determine how much influence quality product, price, brand image and celebrity endorser on consumer purchasing decisions. This type of research explanatory research with quantitative research methods. The data this research is a primary data that collected by using questionnaire and distributed via google form that shared via direct message on social media. The samples in this research amounted to 100 respondents that taken by using purposive sampling techniques. The data in this study were analyzed using multiple linear regression analysis with the SPSS 25.0 tool. The results of this study indicate that variable quality product partially no significant effect on purchasing decision, and variable price, brand image and celebrity endorser partially significant effect on purchasing decision. While the results are simultaneously variable quality product, price, brand image and celebrity endorser significant effect on purchasing decision with value R Square of 0,754 or 75,4%.